Sustainable Business Managing the Challenges of the 21st Century - Fischer, Manuel; Foord, Daniel; Frecè, Jan; Hillebrand, Kirsten; Kissling-Näf, Ingrid; Meili, Rahel; Peskova, Marie; Risi, David; Schmidpeter, René; Stucki, Tobias (SpringerBriefs in Business,, 2023)
This open access book is a compact guide to the development of sustainable business, which has become the central concept in discussions about the future development of humanity and planet earth. It provides basic terminology and concepts on sustainable business and offers insights into a new management paradigm that integrates social and environmental dimensions into business models, strategies, and operations. New business concepts such as the donut economy, the circular economy, social innovation and sustainable leadership are introduced and the book outlines how they influence the way we run businesses today and in the future. This book lays the foundation for new management thinking in business and academia, making it a essential reader for professionals and students alike.